Retrospection of Culture in Religion in The Islands of Nias, Banyak and Simeuleu - Al-Fairusy, Muhajir; Taran, Jovial Pally; Masuwd, Mowafg Abrahem; Idria, Reza; Hemay, Idris; Amirudin, Amirudin (Al-Albab, 2024)
This study focuses and emphasizes on the religious activities of islanders in Banyak Island, Simeulue and Nias. This research aims to find religious models and coexistence strategies in interfaith between island communities. These three islands are geographically close and inhabited by people with different religious identities. This research uses qualitative research with an ethnographic approach, data collection is done through in-depth interviews with informants who live on the three islands. The results showed that island communities have a collective ability to manage diversity to avoid conflict in the name of religion. Identity as an “island community” becomes social capital in interpreting collective identity. The open character of island communities is also a cultural capital that can suppress suspicion of different groups. However, the three island communities also have different characteristics in the religious moderation policy space. Nias Islands with a majority Christian population composition shows a fairly strong attitude of tolerance. The principle of kinship adopted by the Nias community serves to strengthen relations between religious communities. Simeulue Islands, whose majority population is Muslim, also shows a high level of tolerance by giving permission to build houses of worship for Christians who have just arrived in Simeulue in the last two decades. In the context of Pulau Banyak, where the majority of the population is Muslim, tolerance is only seen in the economic, market and fishing industry aspects. On the other hand, tolerance does not apply to permits to build houses of worship. This study also discusses the importance of the role of religious and social actors in strengthening community harmony on the three islands under study.